KONSEP KELUARGA SAKINAH SEBAGAI SOLUSI ALTERNATIF KONFLIK RUMAH TANGGA - Iwan Falahudin (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2021)
There are conflicts between husband and wife that are closed, and some are open, but the ends remain the same, many of which end in divorce. Therefore we need a concept that can be used as a guide to control, reduce, and or at least minimize the possibility of conflicts that can grow, and or even those that have already emerged. This paper was written to describe the concept of the sakinah family according to the government, in this case the ministry of religion. This paper uses a qualitative approach with descriptive methods. The data collection technique is to take data from various digital literacy sources, while the data analysis technique uses deductive techniques. The general conclusion of this study shows that the concept of the sakinah family is a happy family that interacts with a pattern of mutual need, love and affection, standing on a legal marriage, with the ability to carry out its obligations and rights, accompanied by adherence to religious teachings and state law.  This concept is a knowledge that must be understood in depth, accompanied by a strong will to practice it, and a maximum ability to implement it.